Memahami Konsep Emosi dan Konsep Diri Siswa dan Pengaruhnya terhadap Pembelajaran - Habsy, Bakhrudin All; zahra, Kevina Firdaus Az; Sholikah, Erika Badriyahtus; Salma, Tania (Lembaga Yasin AlSys, 2024)
Understanding the role of emotions and self-concept in learning is key to improving the learning process and personal development.The purpose of this study is to determine the concept of emotions and self-concept that affect learning.The method used is a literature study, with the method of collecting library data, reading, recording, and processing research materials.These aspects of self-concept can influence and interact with each other. Emotions and self-concept are not separate in learning. Strong or recurrent emotions can affect a student's self-concept. Conversely, a negative self-concept can affect a student's emotions. In their development, humans have learned social and emotional skills since infancy, where the learning can be obtained from the family environment.With the role of parents and teachers, students get the support they need in the development of healthy emotions and a strong self-concept in themselves.